Iowa RBA, August 10, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for August 10, 1998. Highlights include Eurasian Collared Dove and Little Blue Heron. Includes notes for updates for August 13, August 14, and August 15. Epson - sheet feed/flatbed